Composição dos exsudados florais em áreas com diferentes níveis de severidade abiótica - Silva, Maria Virginia Oliveira da (2020)
The production of floral exudates such as nectar and oils are formed by mixtures of different compounds that may depend on abiotic factors such as water availability and temperature. Thus, the present work proposes to analyze how the abiotic severity affects the composition of the floral exudates. Our hypothesis is that water availability alters the composition of floral exudates so that the quality is lower in more severe environments. We hope that the site with the highest quality of the secreted compounds will be the environment with the greatest water availability compared to the other sites. For this, flowers were collected in three conservation units: Ecological Station of Aiuaba, National Park of Sete Cidades and National Park of Ubajara so that we can carry out histochemical tests and relate the composition of the secretary to his place of study. Our results showed that only the species collected at the Ecological Station of Aiuaba showed a significant correlation between pectin production and water availability. This result helps us to affirm the need for water in a drier environment for the presence of pectin, such as the Park Nacional of Ubajara has a higher water availability than the Ecological Station of Aiuaba during the year there would not be so much need for the presence of a hygroscopic substance in the floral exudate. The secretion of lipid compounds, more expensive to produce and more energetic for the visitor, is not correlated with water availability, but it can be a strategy that influences the preference of pollinators.